Coach-athlete relationship and interpersonal behaviour: Influence in youth athlete continuous participation in sports - Elicot, Siegfried Kent; Java, Moreno Jr; Arias, Elpedio; Orfrecio, Marlene; Tagare, Ruben Jr (UIR Press, 2025)
Background Problems: The coach-athlete relationship and the coach’s behaviour are vital in shaping athletes’ experiences, motivation, and long-term commitment to sports. While previous studies have explored coach-athlete relationships and coaching behaviours, few have examined their combined impact on long-term sports participation. This study seeks to explore how these variables contribute to sustaining youth sports involvement. Research Objectives: The primary objectives of this study are to assess the influence of the coach-athlete relationship and coaches’ interpersonal behaviours on youth athletes’ intention to continue participating in sports and to investigate the relationships between these factors and the overall intention to persist in sports. Methods: A quantitative, descriptive-correlational design was used to examine the relationships between the coach-athlete relationship, coaching behaviours, and youth athletes’ intention to continue in sports. The study involved 66 varsity athletes from a school in Cotabato, Philippines, selected through total enumeration, with data collected using the validated Coach-Athlete Relationship Questionnaire (CART-Q) and Interpersonal Behaviour Questionnaire (IBQ). Data were analysed using frequency counts, weighted means, and Spearman’s rho correlation to assess variable associations and ensure reliability. Findings and Results: The analysis revealed a positive coach-athlete relationship, with athletes expressing strong agreement on trust, respect, and commitment. Perceptions of interpersonal behaviours were similarly positive, particularly regarding coaches’ encouragement in skill development and the enjoyment of time spent with them. However, the study found no significant relationship between the coach-athlete relationship, coaching behaviours, and athletes’ intention to continue participating in sports. Conclusion: Despite positive perceptions of the coach-athlete relationship and interpersonal coaching behaviours. This study found no significant influence on youth athletes’ intention to continue sports participation, highlighting the need for further research on other factors such as athlete motivation, support systems, and environmental conditions that may affect long-term sports engagement.